Pengaruh Pemasaran Media Sosial dan Gaya Hidup yang Dimoderasi oleh Pendapatan terhadap Keputusan Pembelian pada Konsumen Coffee Shout Haurgeulis - Mursyidah Lathifah; Aang Curatman; Dedi Muhammad Siddiq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of social media marketing and lifestyle on consumer purchasing decisions at Coffee Shout Haurgeulis, with income as a moderating variable. The research employed a quantitative method. The sample consisted of 132 respondents, determined using the Slovin formula. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that social media marketing does not have a significant effect on purchasing decisions, while lifestyle has a significant effect. Income is proven to moderate the influence of lifestyle on purchasing decisions but does not moderate the effect of social media marketing on purchasing decisions. The R-square value of 0.307 indicates that purchasing decisions are influenced by the variables in the model by 30.7%, while the remaining variance is explained by other factors outside this study.